Systems science and collaborative information systems theories, practices and new research - Curras, Emilia; Lloret Romero, Nuria, 1966-; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
'This book examines the impact of new information services on day-to-day activities from a range of contemporary technical and socio-cultural perspectives'--Provided by publisher.
1. Vertical integration of science: an approach to including information, knowledge and its organization / Emilia Curr -- 2. What is information?: an enquiry beyond information science from a systemic point of view / Francisco-Javier Garc-Marco -- 3. Information: a multidimensional reality / JosMar Dz Nafr -- 4. Informationism, information and its neuronal theories / Emilia Curr -- 5. The complexity of finding information in collaborative information systems: cognitive needs / Aida Varela and Marilene Lobo -- 6. Understanding user attitudes toward information systems: a grounded theory approach / David A. Jank -- 7. Review and brief history of collaborative systems: taxonomy, services and classification / Nuria Lloret Romero -- 8. Adaptive information retrieval based on task context / Bich-Li{u396E} Doan and Jean-Paul Sansonnet -- 9. Metadata for information retrieval in archives / Vicent Gim{u296E}ez Chornet -- 10. Management systems of user interfaces functionalities in Latin: American Web OPACs / Elsa Barber ... [et al.] -- 11. Academic libraries as complex systems / {u206C}varo Quijano-Sol and Guadalupe Vega-Dz -- 12. Cultural Management 2.0 / Margarita Cabrera M{u296E}dez -- 13. Coagmento: a case study in designing a user-centric collaborative information seeking system / Chirag Shah.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed November 19, 2011).
Keywords: Information science; Information organization; Information retrieval; Information as a science; Metasearching; Open access; Open source software; Collaborative information services; Personal search software; Semantic Web; Collaborative information systems; Vertical integration